AUDITORS’ PROFESSIONAL JUDGMENT IN EVALUATING AUDIT EVIDENCE SUFFICIENCY - Alim Matur Rosyidah; Raden Muhammad Syah Arief Atmaja Wijaya (COMPETITIVE, 2026)
Ensuring sufficient audit evidence is a core aspect of auditors’ professional responsibility in preventing material misstatements. This study aims to obtain empirical evidence on how auditors apply professional judgment in assessing audit evidence sufficiency for revenue accounts. Using a qualitative case study at Public Accounting Firm SS, data were collected through semi-structured interviews with two auditors and validated by document triangulation. Results show that approximately 80% of audit effort is directed toward revenue verification, reflecting its high-risk nature. Auditors apply professional judgment by considering materiality (quantitative threshold of 10% profit or 1% of total assets), audit risk, and transaction complexity. Supervision and team collaboration strengthen judgment reliability and accountability. The study concludes that structured professional judgment enhances evidence sufficiency and audit quality, emphasizing the need for continuous supervision and reflective team discussions.